The odontogenic differentiation of human dental pulp stem cells on hydroxyapatite-coated biodegradable nanofibrous scaffolds. Issue 14 (21st September 2016) - Asghari, Fatemeh; Salehi, Roya; Agazadeh, Marziyeh; Alizadeh, Effat; Adibkia, Khosro; Samiei, Mohammad; Akbarzadeh, Abolfazl; Aval, Negar Abbasi; Davaran, Soodabeh
ABSTRACT: The authors aimed to design nanofibrous (NF) scaffolds that facilitate odontogenic and osteogenic differentiation of human dental pulp-derived mesenchymal stem cells (DPSCs) in vitro. For this purpose, hydroxyapatite (HA)–loaded poly (L-lactic acid)/poly (ϵ-caprolactone) (PLLA:PCL 2;1) blend NFs were prepared using the electrospinning method. Alizarin red activity and cell viability were evaluated by MTT assay, and SEM revealed the proliferation properties of NF scaffolds. QRT-PCR results demonstrated that HA-loaded PLLA/PCL can lead to osteoblast/odontoblast differentiation in DPSCs through the up-regulation of related genes, thus indicating that electrospun biodegradable PCL/PLA/HA has remarkable prospects as scaffolds for bone and tooth tissue engineering. GRAPHICAL ABSTRACT: